Surface functionalization of carbon nanomaterials by self‐assembling hydrophobin proteins1. Issue 1 (23rd October 2012) - Yang, Wenrong; Ren, Qin; Wu, Ya‐Na; Morris, Vanessa K.; Rey, Anthony A.; Braet, Filip; Kwan, Ann H.; Sunde, Margaret
Abstract Class I fungal hydrophobins are small surface‐active proteins that self‐assemble to form amphipathic monolayers composed of amyloid‐like rodlets. The monolayers are extremely robust and can adsorb onto both hydrophobic and hydrophilic surfaces to reverse their wettability. This adherence is particularly strong for hydrophobic materials. In this report, we show that the class I hydrophobins EAS and HYD3 can self‐assemble to form a single‐molecule thick coating on a range of nanomaterials, including single‐walled carbon nanotubes (SWCNTs), graphene sheets, highly oriented pyrolytic graphite, and mica. Moreover, coating by class I hydrophobin results in a stable, dispersed preparation of SWCNTs in aqueous solutions. No cytotoxicity is detected when hydrophobin or hydrophobin‐coated SWCNTs are incubated with Caco‐2 cells in vitro. In addition, we are able to specifically introduce covalently linked chemical moieties to the hydrophilic side of the rodlet monolayer. Hence, class I hydrophobins provide a simple and effective strategy for controlling the surfaces of a range of materials at a molecular level and exhibit strong potential for biomedical applications. © 2012 Wiley Periodicals, Inc.